Penerapan Model Pembelajaran Problem Posing dengan Metode Eksperimen untuk Meningkatkan Hasil Belajar Fisika pada Siswa Kelas VIII SMP Negeri 19 Mataram Tahun Pelajaran 2015/2016 - Sofiana Rahmiatun Hatmawati; Joni Rokhmat; Kosim Kosim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
This Classroom action research (CAR) aimed to establish strategy implementation model of problem posing learning with experiment method to increase physics learning outcome on VIII grade of SMPN 19 Mataram school year 2015/2016. This research was conducted two cycles, each consisting of two meeting that includes four phases, plan, action, observation, and reflection. The percentage ofclassical completeness learning outcomes on cognitive domain from the first cycle to the second has increased from 75.00% become 87.50% with the average value for each cycle is 72.66 and 78.28, on affective from the first cycle to the second has increased from 67.97 become 78.12 (good enough to be very good), and psychomotor domain from the first cycle to the second has increased from 12.22 become 15.58 (competent become more competent). It was concluded that to increase learning outcome, strategy implementation model of problem posing learning with experiment method namely: 1) giving the reward in the form of gifts and addition of value to student who are active, orderly, and not create a disturbance during the learning activities, 2) give attention and guidance in the form of an explanation about subject matter and learningactivities to be performed, 3) gives some examples of making the problem and explaining it in detail, and also 4) pointing at random members of each group to the presentation.